Pengaruh Inovasi Produk, Promosi dan Sertifikasi Halal Terhadap Keputusan Pembelian Produk Somethinc (Studi Pada Mahasiswa FEB Universitas Islam Malang) - Ula, Jauza’ Nuril; Khalikussabir, Khalikussabir; Arsyianto, Muhammad Tody (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to test and determine the effect of product innovation, promotion and halal certification on purchasing decisions for Somethinc products (case study on students of the Faculty of Economics and Business, Islamic University of Malang). This research is a type of quantitative research. The sampling method used is purposive sampling. The sampling technique using the formula from Malhotra with the results of the calculation of 75 samples. To solve the problems in this study using SPSS assistance with validity tests, reliability tests, normality tests, multiple linear regression analysis, multicollinearity tests, heteroscedasticity tests, F tests, and t tests. The results showed that simultaneously the variables of Product Innovation (X1), Promotion (X2), and Halal Certification (X3) had a significant effect on Purchasing Decisions (Y). Partial research results show that Product Innovation (X1), Promotion (X2) and Halal Certification partially have a positive and significant effect on Purchasing Decisions (Y). Keywords: Product Innovation, Promotion, Halal Certification, Purchasing Decisions.